The Ability of Dissolved Oxygen and Biochemical Oxygen Demand Parameters to Self-purify in the Garang River - Junaidi Junaidi; Ika Bagus Priyambada; Nindya Venoreza (Universitas Diponegoro, 2021)
Garang River is administratively located in Semarang Regency, Kendal Regency, and Semarang City. Population growth and the number of community activities around the river can affect the water quality of the Garang River. Wastewater discharged into the Garang River will reduce water quality. The number of pollutants that enter the river changes the quality of river water until it reaches a pollutant level that exceeds the quality standard. The purpose of this study was to determine the self-purification ability of the Garang River using the Streeter-Phelps method based on DO and BOD parameters to obtain an oxygen sag curve for oxygen reduction. There are 3 monitoring stations that are located in the upstream segment of the Garang River. The value of the deoxygenation constant (K) in segment 1 is around 0.340, the reaeration constant (R) is 3.433, and the value of fs = 10.103. While in segment 2. the value of K is 0.335, R is 3.417, and fs is 10.194. It is revealed that segment 1 and segment 2 of the Garang River have not yet experienced optimal natural purification because they are still in the degradation zone.